Analysis of a role of hypusinated eukaryotic initiation factor 5A (EIF5A) and its isoform EIF5A2 in embryonic stem cell self-renewal and differentiation. - Lee, Su Qi. (2013)
Embryonic stem cells (ESCs) are pluripotent cells which are characterized by their unique ability to self-renew and generate all differentiated cell types. The polyamine regulator AMD1 (Adenosylmethionine Decarboxylase), was recently shown to be an essential self-renewal factor in ESCs (Zhang et al., 2012). Down regulation of AMD1 leads to a reduction in spermidine levels and subsequently a decrease in the levels of hypsuinated Eukaryotic Initiation Factor 5A (EIF5A) (Zhao et al., 2012). This led to our hypothesis that EIF5A and its isoform EIF5A2 could be critical downstream effectors of AMD1 in promoting maintenance of the ESC state. To address this question, we analysed the gene expression patterns of EIF5A and EIF5A2 in ESCs and differentiated ESCs and saw no change before and after differentiation. To investigate the roles of EIF5A and EIF5A2 in ESCs, we used siRNAs targeting EIF5A and EIF5A2 mRNAs. The experiment was inconclusive as no knockdown in EIF5A and EIF5A2 mRNA levels was achieved. To further address the role of EIF5A and EIF5A2 in ESCs, we then treated ESCs with the EIF5A and EIF5A2 inhibitor GC7 to monitor effects on cell proliferation, viability and differentiation. We observed a decrease in cell proliferation after GC7 treatment but no detectable effects on pluripotent state of ESCs. Our data, though preliminary suggests EIF5A and EIF5A2 may play a role in ESC proliferation.